IDENTIFICATION ET ANALYSE DES BESOINS - Anna Vougiouklidou (European Scientific Journal, ESJ, 2013)
The teaching of a foreign language, English, French and German, is compulsory at the University of Piraeus. We teach French as a language of specialty to a homogeneous “public” (level B1) but in this article we will try to justify the necessity to identify and analysis the needs of our “public”The identification of the above needs is a constant step taken before as well as during the learning process and is rendered to objectives, content, action and schedule.Questionnaires, interviews etc, are among the tools we use in order to collect the information. This article presents such a questionnaire.